Phenolic and sensory profiles distinguish Malbec wines according to intra-vineyard soil effective depth across different vintages - Mezzatesta, Daniela Silvia (2025)
High-elevation viticulture in Mendoza is increasingly recognised among the world’s top wine regions. This unique terroir combines heterogeneous alluvial soils, intense solar ultraviolet-B (UV-B) radiation and cool night temperatures, creating distinct phenotypic expressions of Vitis vinifera L., particularly Malbec, Argentina’s most important grapevine variety. This threeyear study investigated intra-vineyard soil heterogeneity by evaluating the impact of contrasting soil profiles of shallow (SS) and deep (DS) soils on the qualitative and quantitative phenolic profiles, antioxidant capacity, and sensory attributes of Malbec wines. The experiment was carried out on a 1450 m a.s.l. vineyard selecting parcels with different effective soil depth (SS: 0–0.45 m; DS: 1–1.5 m) and physicochemical properties, but matching viticultural management and irrigation. Ripening occurred earlier in SS, and grapes were harvested at comparable °Brix across soil types; however, harvest °Brix varied by season. Winemaking was conducted in replicates using standardised procedures. Two-way ANOVA revealed significant main effects of soil type and vintage, plus their interaction. While vintage effects were significant, SS consistently produced wines with higher dihydroxylated and non-acylated anthocyanins, as well as greater antioxidant capacity (ORAC) and total anthocyanin content in two of the three vintages. Low-molecular-weight polyphenols (LMWPs) such as polydatin (a stilbene), astilbin (a dihydroflavonol), and quercetin (a flavonol) were significantly higher in SS wines, whereas p-coumaric acid (a hydroxycinnamic acid) and (–)-epicatechin (a flavanol) predominated in DS wines. Sensory analysis revealed that expert tasters consistently distinguished and preferred SS wines, which were perceived as more acidic and astringent. In contrast, DS wines were characterised by sweeter flavours and jam, green pepper, leather, and earthy notes. The perception of mineral aroma did not differ between soil types. These findings contribute to a better understanding of how soil profile influences Malbec wine composition and sensory descriptor expressions in a consistent manner, that is, under variable seasonal conditions, fundamental for terroir-driven wine production.